2011
DOI: 10.2320/matertrans.l-mz201121
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cu Addition on Behavior of Nanoclusters during Multi-Step Aging in Al-Mg-Si Alloys

Abstract: Two types of nanoclusters, i.e. Cluster (1) and Cluster (2), play a strongly important role in the bake-hardening (BH) response in Al-Mg-Si alloys. Different formation behaviors of two types of nanoclusters were studied by means of hardness, differential scanning calorimetry (DSC), electrical resistivity measurement, transmission electron microscopy (TEM) and high resolution TEM observation in the both Cu-free and Cuadded Al-Mg-Si alloys. As the results, Cluster (1) formed during natural aging at room temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 19 publications
3
43
0
Order By: Relevance
“…The higher hardness in the Cu-added alloy is obtained than that in the Cu-free alloy during over-aging regardless of the NA time. The over-aging behavior is confirmed at the previous study 24,25) since the copper atoms segregated at the interface between the precipitates and the aluminum matrix suppress the growth of the precipitates. 19,33) Figure 7 shows the changes of the electrical resistivity during aging at 170°C with the different heat-treatment conditions in the Cu-free alloy.…”
Section: Resultssupporting
confidence: 71%
See 3 more Smart Citations
“…The higher hardness in the Cu-added alloy is obtained than that in the Cu-free alloy during over-aging regardless of the NA time. The over-aging behavior is confirmed at the previous study 24,25) since the copper atoms segregated at the interface between the precipitates and the aluminum matrix suppress the growth of the precipitates. 19,33) Figure 7 shows the changes of the electrical resistivity during aging at 170°C with the different heat-treatment conditions in the Cu-free alloy.…”
Section: Resultssupporting
confidence: 71%
“…25,30,3437) However, the increase in the hardness during aging at 170°C after NA is newly found during the middle stage. Namely, three stages of the two-step aging behavior with the NA time are first found in this study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The control of nanoclusters by the microalloying elements as well as the heat-treatment histories becomes extremely important in terms of the nanocluster formation at the early stage of the phase decomposition. 8,9) Furthermore, Otsuka et al 10) reported the effect of alloy composition on the formation of nanoclusters and nanoprecipitates. They concluded that the formation of nanoclusters markedly depends on the Mg, Si concentration and the Mg/Si ratio.…”
Section: Introductionmentioning
confidence: 99%